IMPROVING TEACHER ABILITY IN MI (MADRASAH IBTIDAIYAH) TO MAKE PLAN OF LEARNING IN EAST DISTRICT OF JATITUJUH - Eti Jaskarti (PrimaryEdu : Journal of Primary Education, 2018)
The purpose of this study is to observe: 1) the final ability of MI teachers to make / compile RPP with discovery learning, problem based learning, and project based learning model according to the provision in the 2013 curriculum after being given the drill method using job sheet. 2) early ability of MI teachers to make / compile RPP with discovery learning model, problem based learning, and project based learning according to the provision in curriculum 2013 before being given practice / drill method using job sheet. Data collection during the workshop on Curriculum Implementation 2013 for 22 hours (3hari). Alternative strategy taken in this research using experimental method with Pre-Experimental Design form. While the design used One-Group Pretest-Posttest Design. In this design there are pretest before being treated, and posttest after being given treatment using drill method, the study population is all the participants of workshop on the implementation of curriculum 2013 which amounted to 34 MI teachers in one class. Posttest implemented towards the end of the workshop. Based on the results of the study and discussion are described as follows: 1) the final ability of MI teachers is good with average posttest 77,082 with variance 31,780 and Corelasi 0,934> 0,05. 2) the initial ability of MI teachers is still in doubt with pretest averages of 55.440 and variance of 12,678, better ending ability than initial ability and with Asymp.Sig (2-tailed) = 0.005 <0.05 means there is a difference in ability beginning and end. In the end, it can be concluded that the practice / drill method using job sheet in the workshop can improve the ability of MI teachers to arrange RPP with discovery learning, problem based learning, and project based learning model according to the provision in the 2013 curriculum, in other words the method of drill / drill classified effective in the preparation of RPP based on the provisions according to the curriculum 2013.